Indeno[1, 2‐b]carbazole as Methoxy‐Free Donor Group: Constructing Efficient and Stable Hole‐Transporting Materials for Perovskite Solar Cells. (16th September 2019) - Wang, Jialin; Zhang, Heng; Wu, Bingxue; Wang, Zhihui; Sun, Zhe; Xue, Song; Wu, Yongzhen; Hagfeldt, Anders; Liang, Mao
Abstract: With perovskite‐based solar cells (PSCs) now reaching efficiencies of greater than 20 %, the stability of PSC devices has become a critical challenge for commercialization. However, most efficient hole‐transporting materials (HTMs) thus far still rely on the state‐of‐the‐art methoxy triphenylamine (MOTPA) donor unit in which methoxy groups usually reduce the device stability. Herein, a carbazole‐fluorene hybrid has been employed as a methoxy‐free donor to construct organic HTMs. The indeno[1, 2‐b]carbazole group not only inherits the characteristics of carbazole and fluorene, but also exhibits additional advantages arising from the bulky planar structure. Consequently, M129, endowed with indeno[1, 2‐b]carbazole simultaneously exhibits a promising efficiency of over 20 % and superior long‐term stability. The hybrid strategy toward the methoxy‐free donor opens a new avenue for developing efficient and stable HTMs. Abstract : Balanceakt : Der Indeno[1, 2‐ b ]carbazol‐Donor kombiniert nicht nur die Merkmale von Carbazol und Fluoren, sondern zeigt auch eine exzellente thermische Stabilität und hohe Lochmobilität infolge seiner sperrigen planaren Struktur. Lochtransportmaterialien auf Basis dieses Methoxy‐freien Donors sind zugleich hoch effizient und stabil und damit vielversprechend für die Entwicklung effizienter, stabiler Perowskit‐Solarzellen.